1987
DOI: 10.1146/annurev.pa.27.040187.001205
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Drug Design

Abstract: Progress in genetic engineering has increased the need for, while advances in computational hardware have removed barriers impeding, the development of appropriate computational tools to assist in the understanding of molecular interactions. Advancements both in techniques and in broadening application have been clearly demonstrated. Further development requires progress in the fundamental aspects of theoretical chemistry as well as an increased base of experience in choosing the appropriate set of assumptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
96
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(99 citation statements)
references
References 61 publications
2
96
0
1
Order By: Relevance
“…The most popular way of aligning molecules follows an iterative adjustment of torsion angles with a subsequent least-squares superposition of key atoms of a pharmacophore (derived for the particular class of compounds under consideration). More complete and objective is the active-analog approach [2,3] which generates plausible molecular geometries showing a common orientation of the pharmacophoric groups. If some hypothesis about the active-site conformation is given, a multiple-flexible fit can be performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular way of aligning molecules follows an iterative adjustment of torsion angles with a subsequent least-squares superposition of key atoms of a pharmacophore (derived for the particular class of compounds under consideration). More complete and objective is the active-analog approach [2,3] which generates plausible molecular geometries showing a common orientation of the pharmacophoric groups. If some hypothesis about the active-site conformation is given, a multiple-flexible fit can be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Three different classes of mimics, formally orienting a positively charged nitrogen toward the charged portion in the sterol reference cation, are shown with their I50 values for the inhibition of A14-reductase from Ustilago maydis: 4-t-butylphenylpiperidines (1), t-butylbenzyl-(t-butyl)cyclohexylamines(2), and 4-t-butylbenzylmethylaminodecalins (3).…”
mentioning
confidence: 99%
“…Therefore, HA is a promising target for developing anti-influenza drugs, which block the initial entry step of viral life cycle. Recently, molecular modeling and computational chemistry based computer-aided drug design provided great help for modern drug development (Marshall, 1987). Software programs such as Auto Dock were widely used to search potential inhibitor for protein targets (Morris, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This idea was supported by studies investigating the proposed agonist binding site of the receptor which suggested that a phenylalanine residue was a key site of interaction for agonist compounds [8] and this proposal is in accord with a generalized pharmacophore model for central nervous system drugs and their receptors [9]. A more recent model developed by Hacksell and Mellin [10] has re-examined the 'Active Analogue Approach' [3] to propose a pharmacophore which includes newly-identified potent nicotinic agonists. In particular, these authors examined agonist conformations that can be used to explain stereoselective interactions of agonists with the nicotinic receptor [10].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of new potent and selective ligands and the development of computerized techniques for studying molecular conformation have recently been used to test the validity of this pharmacophore model. For example, Sheridan et al [2] developed a nicotinic receptor pharmacophore using a modification of Marshall's 'Active Analogue Approach' [3] and these studies served to corroborate and extend the pharmacophore model of Beers and Reich [1].…”
Section: Introductionmentioning
confidence: 99%